Chitosan Complexes with Gallic Acid Obtained in the Solid State - Akopova, T. A.; Ivanov, P. L.; Svidchenko, E. A.; Kurkin, T. S.; Popyrina, T. N.; Svischeva, N. B.; Zakharevich, A. A.; Malyk, B. V.; Khavpachev, M. A. (Applied biochemistry and microbiology, 2025)
In this paper, we describe mechanochemical approach as an environmentally friendly method for the functionalization of chitosan with gallic acid. Coupling with a polysaccharide is one way to stabilize antioxidants and improve their bioavailability. Since gallic acid is a solid compound with limited solubility and a high melting point (220–240°C), it was of interest to conduct its interaction with chitosan using solid-state synthesis technique under shear deformations. The experimental conditions were selected using a pilot twin-screw extruder designed for processing solid dispersions. DSC and WAXD data were used for study of response of the system to shear deformation. The insertion of gallate groups onto the polymeric backbones was confirmed by 1 H NMR, FTIR and UV–vis analyses. It was found that gallate groups are predominantly linked to chitosan via salt bonds. Depending on the synthesis conditions, the amount of bound gallic acid was more than 600 mg per 1 g of chitosan. In contrast to the physical mixing of components, the resulting products swelled well and partially dissolved in water, and tended to form aggregates with an average size of 206 ± 36 µm in aqueous media. It was shown that the obtained compositions have moderate antibacterial activity against Gram-positive bacteria ( Bacillus subtilis ). The proposed approach is promising for the creation of biologically active solid compositions capable of being processed into final products due to ultradispersion and gelation in water with the possibility of use in the form of hydrogels, sprays, and sponge materials.